Celebrating hydrologic science: The "Science is Essential" collection. Issue 7 (13th July 2017) - Clark, Martyn P.; Luce, Charles H.; van Meerveld, H. J. (Ilja)
Abstract: Water Resources Research published nine commentaries in the AGU "Science is Essential" collection. The goal of these papers is to celebrate the advances in hydrologic science, to show how hydrologic science is essential for society, and to illustrate how hydrologic science has influenced policies. Here we provide a brief introduction to these papers, to encourage you to explore them in full. Key Points: Many of the most meaningful problems necessarily engage scientists from multiple fields to conduct rigorous interdisciplinary science Science is done to help people and consequently requires scientists to effectively communicate science advances to society Science is needed to objectively inform the policy process